Expression analysis of MHC class II DRB3 gene in mastitis affected indicus and crossbred cattle - LOAT, SHUBHAM; KUMARI, NAMITA; DHILOR, NITIKA; KUMAR, ANURAG; KUMAR, NARESH; NIRANJAN, S K; SODHI, MONIKA; MUKESH, M; KATARIA, R S (The Indian Journal of Animal Sciences, 2020)
Expression analysis of immune response genes in the mammary gland tissues of both healthy and infected animals help to explain the genetic basis of differential immune response. This study was conducted to analyze the differential expression of MHC class II DRB3 gene, in mastitis-affected and healthy animals of indicus (Sahiwal) and crossbred (Karan Fries) cattle. Real-time PCR was performed on the cDNA synthesized from the RNA isolated from PBMCs of the mastitis and healthy animals. However, no significant difference was observed in the expression of DRB3 in the two populations. The results point towards polymorphism supposed to be playing major role in differential immune response, rather than the expression of DRB3 gene as far as state of udder health is concerned.